Request for the disbursement of the advance for material procurement of finishing work of BRAC University new campus project - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the request for the disbursement of the advance for material procurement of finishing work of BRAC University new campus project.